Taking up the challenge of evidencing value in educational development: from theory to practice*. Issue 3 (2nd July 2016) - Bamber, Veronica; Stefani, Lorraine
Abstract: Measurable targets, key performance indicators, value for money – whatever we may think of the 'impact agenda', it looks like it is here to stay. Are we trapped in a positivist, new managerialist spiral of demonstrating the value of our work, or can we take the lead in reframing the discourse on how educational development proves its worth? This paper suggests that how we gather and present evidence is currently not fit for the purpose of demonstrating the value of educational development to our institutions. The paper argues that reconceptualising 'impact' as 'evidencing value' could release us from inadequate or instrumental approaches to evaluation. Evidencing does involve measuring and evaluating, but it also acknowledges the role of judgement, experience, and contextual knowledge in determining what needs to be evaluated, and how. It allows us to reconfigure what can legitimately be included in our heterogeneous mix of evaluation data. Examples of frameworks which might support us in evidencing value are offered.